Unveiling the Nature of Galactic TeV Sources with IceCube Results - V. Vecchiotti; F. L. Villante; G. Pagliaroli (The Astrophysical Journal Letters, 2023)
IceCube collaboration reported the first high-significance observation of the neutrino emission from the Galactic disk. The observed signal can be due to diffuse emission produced by cosmic rays interacting with interstellar gas but can also arise from a population of sources. In this paper, we evaluate both the diffuse and source contribution by taking advantage of gamma-ray observations and/or theoretical considerations. By comparing our expectations with IceCube measurements, we constrain the fraction of Galactic TeV gamma-ray sources (resolved and unresolved) with hadronic nature. In order to be compatible with the IceCube results, this fraction should be small, or the source proton energy cutoff should be well below the cosmic-ray proton knee. In particular, for a cutoff energy equal to 500 TeV, the fraction of hadronic sources should be less than ∼40% corresponding to a cumulative source flux Φ _ν _,s ≤ 2.6 × 10 ^−10 cm ^−2 s ^−1 integrated in the 1–100 TeV energy range. This fraction reduces to ∼20% for energy cutoff reaching the cosmic-ray proton knee around 5 PeV.